UPAYA PENINGKATAN KEDISIPLINAN DAN KINERJA GURU MELALUI PEMBINAAN INDIVINDU - Desi Anggraini (Manajer Pendididikan, 2016)
The purpose of this study are to describe how to increase the discipline through individual coaching, to describe whether the application indivindu coaching can improve the performance of teachers, to describe how is the process of applying coaching indivindu to improve discipline and performance of teachers. Data were collected by the instrument scale discipline andteacher performance assessment and observation sheet. Action Research was used in this research. It can be concluded that the discipline and teacher performance increase in cycle 1, 2 and 3. It can be concluded that coaching indivindu can improve discipline and teacher performance.Keywords: discipline, performance, coaching indivindu